Natural products - Bhat, S. V. ([S.l.] : Alpha Science International, Ltd, 2009)
The major aim of this book is to provide an easy to read overview of chemistry and applications of natural products. It includes fourteen chapters covering most of the aspects of natural products chemistry. The result of the authors' present endeavors is the unique monograph that presents comprehensive information on occurrence, chemistry, biosynthesis and applications of various natural products. First twelve chapters cover general introduction, nomenclature, occurrence, isolation, detection, structure elucidation by degradation, biosynthesis, synthesis, biological activity and commercial applications, if any, of the compounds mentioned in each topic. Some fascinating syntheses of natural products and applications of enzymes in organic synthesis are discussed in chapters 13 and 14 respectively. In addition, there is general introduction for natural products. Therefore the present textbook will be useful for students, other researchers and industry.
Keywords: chemistry,natural products